ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL ARITMATIKA SOSIAL PADA SISWA KELAS VII - Fitriani, Fany Nur; Kadarisma, Gida (IKIP Siliwangi, 2022)
The research was aimed at analyzing student's difficulties in resolving social arithmetic on 7th grade class. The method was qualitative descriptive. In one of West Bandung MTSN with 20 students on 7th grade class 2020-2021 school year as subject. The sampling was giving a written test of six questions. After that, the answer will be analyzed. That data were analyzed by Data Reduction, Data Presentation, and Drawn a Conclusion. Result of the research showed that the student's difficulties are 1) understanding the question 2) determining the correct formula 3) the student less precise in answer the questions and 4) lack of understanding concepts. Result of this research hopes that teachers can lead and help the student's difficulties, so that students can improve their math skills especially social arithmetic.